Ecotourism Potential in Meratus Geopark, South Kalimantan - Normelani, Ellyn; Riadi, Selamat; Noortyani, Rusma; Endarto, Endarto; Nayan, Nasir (Graduate School, Universitas Brawijaya, 2021)
Ecotourism development in Mt. Meratus, South Kalimantan, is crucial to support the future development and forest use in the South Kalimantan area. Ecotourism provides a mechanism to use forest resources sustainably while at the same time provides opportunities for local economic growth. This paper aims to describe the potential resources of Mt. Meratus to support the ecotourism program in South Kalimantan. The development of ecotourism in Mt. Meratus has been crucial since the area has a high level of geo-biodiversity and cultural resources, which are important for the future human being. Protecting and promoting indigenous knowledge of the community in the Mt. Meratus geo-site area are important to support sustainable development programs, including the development of ecotourism as one of the practices of responsible travels to the natural ecosystem.Keywords: biodiversity conservation, geotourism, Mt. Meratus Kalimantan.